1993
DOI: 10.1242/dev.118.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct populations of prestalk cells within the tip of the migratory Dictyostelium slug with differing fates at culmination

Abstract: The ecmA gene of Dictyostelium encodes an extracellular matrix protein and is selectively expressed in prestalk cells. We show that its promoter contains discrete elements that direct expression in different subpopulations of prestalk cells. Prestalk(pst)A cells occupy the front half of the prestalk region. Expression in pstA cells requires DNA sequences close to the cap site of the gene and a separate, upstream region that acts in combination with the gene proximal sequences. PstO cells are situated in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“… Initial studies of the genes are indicated by locus tag superscripts: * studied here; # ( Kin et al, 2018 ); %:( Chen et al, 2017 ); $: ( Ceccarelli et al, 1991 ); £:( Early et al, 1993 ); &:( Jermyn and Williams, 1991 ). For StaE basal disc expression was initially not reported ( Kin et al, 2018 ), but was detected in replicate experiments ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Initial studies of the genes are indicated by locus tag superscripts: * studied here; # ( Kin et al, 2018 ); %:( Chen et al, 2017 ); $: ( Ceccarelli et al, 1991 ); £:( Early et al, 1993 ); &:( Jermyn and Williams, 1991 ). For StaE basal disc expression was initially not reported ( Kin et al, 2018 ), but was detected in replicate experiments ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 29 novel RNAseq informed cell-type markers that were validated here and previously ( Kin et al, 2018 ) ( Table 1 ), we selected 18 genes that showed expression patterns representative for the whole set to study regulation by added stimuli. This subset was supplemented with ecmA and ecmB expressed from their full promoters ( Jermyn and Williams, 1991 ) and from the pstO and pstA regions for ecmA ( Early et al, 1993 ) and the ST-region for ecmB ( Ceccarelli et al, 1991 ), and with the c-di-GMP responsive stalk gene staC and unresponsive gene staD , that were both detected in an RNAseq study of a dgcA knock-out ( Chen et al, 2017 ). Pools of Ax2 cells, freshly transformed with gene fusions of lacZ to the promoters of all markers were developed on non-nutrient agar to a stage just before the gene in question started to be expressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B , schematic illustration of the starvation-induced developmental cycle of Dictyostelium discoideum . Prestalk cells and anterior-like cells are labeled blue ( 83 ). The life cycle is renewed when spores from a fruiting body germinate to become feeding amoebae.…”
mentioning
confidence: 99%